Analysis of a micro photovoltaic/thermal – PV/T system operation in moderate climate. (July 2019) - Bigorajski, Jarosław; Chwieduk, Dorota
Abstract: The paper analyses the possibility of application of PV/T systems in moderate climate conditions. Experimental part of research studies has been developed in Patras, Greece, in October–November. In that time climatic conditions in Greece are similar to summer (warmest) weather conditions in Poland. Some aspects of Polish climatic conditions, especially of solar radiation availability are presented. The liquid single glazed PV/T module has been selected for consideration as the most suitable for described climatic conditions. Experimental outdoor stand with such PV/T module has been designed and constructed to determine its energy performance. A mathematical model of the photovoltaic/thermal solar system operation is presented. Existing formula for determination of the PV/T temperature during its operation has been validated by experimental studies. As a result the correction - design factor has been introduced to the formula. It helps to take into account the design (number of covers) of the PV/T module, when its energy performance and operation are determined through simulation studies. Simulation studies of the dynamics of a microscale PV/T system supplying energy (electricity and heat to Domestic Hot Water system) to a standard single-family house has been performed using own numerical code. Selected results of simulation studies of the operation of different cases (sizes) of PV/T systems are described. Simulation studies of operation of the PV/T systems in micro scale application in high latitude countries show, that for 2 months of a year, in December and January, more electrical than thermal energy is generated by the PV/T system. In summer problems with too high temperature of the working fluid of the PV/T module can occur. As a result, the electrical efficiency decreases. In Polish climatic conditions a PV/T system should be provided with a continuous heat removal system to assure efficient operation of the system. Highlights: Among different types of PV/T modules the liquid single glazed type is the most recommended for high latitude countries. The design of the PV/T module should be taken into account, when the PV effective temperature is calculated. Correction factor in equation determining the PV effective temperature in the liquid glazed PV/T module has been formulated. Problems with too high temperature of a working fluid of the PV/T module in summer in high latitude countries. Higher electricity than thermal energy gains in PV/T system in winter in high latitude countries.